Los albores del derecho internacional en la Universidad de Buenos Aires : la enseñanza de la materia según Antonio Sáenz - Padín, Juan Francisco (2016)
This research refers to the work of Antonio Sáenz as a professor of Natural Law and Law of the Nations between 1822 and 1823. The paper stresses on the impact of this course on the teaching of International Law at the beginning of the University of Buenos Aires. This paper considers different levels of analysis involving the teaching of the subject with the purpose of achieving a comprehensive study of the work of Sáenz. According to him, these areas were essential to the contents of the course. The analysis is divided into two categories, addressing both historical and academic aspects, with the purpose of establishing a complete vision of the context in which the University of Buenos Aires was founded (1821). With the aim of establishing the educational relevance and contributions to legal science made by professor Sáenz, his work is confronted here with the developments offered by other relevant authors of international law (such as Jeremy Bentham). Also, this research deals with the innovations that these teachings could have had in the discipline, especially considering the text written by Sáenz for this course: Elements of Natural Law and the Law Of Nations (1823).